China’s Cooperation in Latin America: Implications for Development Assistance - Erthal Abdenur, Adriana; Marcondes de Souza Neto, Danilo (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2013)
Over the past decade, Chinese cooperation in Latin America and the Caribbean has gained momentum, propelled not only by growing trade, but also by increasingly diverse political, security, technological, and cultural ties. While this cooperation has brought tangible benefits, it has also generated new dynamics of competition, including among the actors involved in development assistance. This article examines some of the effects of Chinese cooperation, looking at the risks and opportunities as well as other donors’ reactions to China’s involvement. Our analysis highlights four key trends that may be intensified by an upsurge in Chinese cooperation: priority shifts, donor displacement, civil society exclusion, and regional fragmentation.